Update on pathogenesis, diagnostics and therapy of nonalcoholic fatty liver disease in children - Flisiak-Jackiewicz, Marta; Lebensztejn, Dariusz (Clinical and Experimental Hepatology, 2019)
Nonalcoholic fatty liver disease (NAFLD) represents the most common cause of chronic liver disease. Increasing prevalence of NAFLD in children may be the cause of unfavorable metabolic implications and development of end stage liver disease. NAFLD is a “multiple-hit” disease mediated by several metabolic, environmental, genetic and microbiological mechanisms. Additionally, lipotoxicity, oxidative stress and inflammation predispose to progressive liver damage. According to current guidelines, liver biopsy is an imperfect gold standard for NAFLD diagnosis, but due to its invasive character its use is limited in children and it should be performed only in children who need exclusion of coexisting diseases. Noninvasive methods should be preferred and current research is focused on serum markers and novel imaging or elastographic techniques. Therapeutic approaches for NAFLD are currently focused on lifestyle modification, insulin resistance, dyslipidemia, oxidative stress and the gut microbiome. However, a number of clinical studies on novel therapeutic molecules are ongoing.